Aspectos bioquímicos e etnofarmacológicos do látex de Himatanthus drasticus Mart. (Plumel) - Matos, Mayara Patrícia Viana de (2013)
Himatanthus drasticus (Apocynaceae) is traditionally used in folk medicine in Northeastern Brazil. The plant is wildly distribuited from Guianas until Southeast Brazil. Latex obtained by cutting its stem bark is mixed with water and extensively sold in public markets. People use Janaguba milk (“Leite de Janaguba”- LJ) to treat or prevent different inflammatory disorders such as gastritis, ulcers as well as cancer, among other uses. Despite, there is not enough scientific data confirming these pharmacological properties. In this work, Janaguba milk was preliminarily investigated in an attempt to validate its anti- inflammatory activity. Its major protein fraction (HdLP) was assessed for the presence of anti- inflammatory, anti-nociceptive and toxicological effects. LJ inhibited the inflammatory response induced by carrageenan in rats (98%, p < 0.05), whereas HdLP did it independent of the route of administration. HdLP significantly reduced the infiltration of neutrophils into the peritoneal cavity (96%, p < 0.05) concomitant with increased nitric oxide synthesis in plasma and decrease of pro-inflammatory cytokines IL- 1 and TNF-α in peritoneal fluid. This fraction also prevented vacuolization and Kupfer cell hyperplasia caused by carrageenan in liver. Further, the anti-inflammatory properties were shown to be associated with the protein fraction of LJ. HdLP exhibited anti-inflammation, even after heat-treatment (100 °C, 30 min) or proteolysis. Moreover, a pro-inflammatory effect was observed after HdLP treatment. It also suppressed abdominal constrictions in acetic acid-treated mice and reduced paw licking induced by formalin, both in a dose-dependent manner. An acute toxicological evaluation demonstrated no toxic effects after 14 days from LJ and HdLP administration by oral route even when high doses were tested. A qualitative phytochemical analysis showed the absence of lupeol and presence of saponinas, tannins and free steroids in HdLP. However, pharmacological properties are probably not related to them. It is therefore concluded that the latex of Himatanthus drasticus exhibits both the anti-inflammatory and anti-nociceptive activities claimed by its users. The protein fraction of the latex is an important contributor to the pharmacological properties of LJ. Resistance to heat and proteolytic treatment can explain the effectiveness of HdLP even when administered orally. The absence of toxic effects by oral route confirms the potential use of this plant as a phytotherapic agent.